Strategizing Economic Revival in Mandalika through A One-Stop Digital Collaborative Marketing Platform Upholding Local Wisdom - Ario Yudo; Nadiyasari Agitha; Fitri Bimantoro; Nuraqilla Waidha Bintang Grendis (Institute for Research and Community Services, Udayana University, 2025)
In the era of digital transformation, information technology plays a pivotal role in shaping economic landscapes and cultural preservation strategies. This research introduces an innovative approach to economic revitalization in Mandalika, Indonesia, through a One-Stop Digital Collaborative Marketing Platform, fully integrated with the NTBmall app, a key digital initiative by Dinas Perdagangan NTB for promoting local products. This symbiotic blend of cutting-edge digital solutions and Mandalika's rich local wisdom forms the core of our strategy, aiming to rejuvenate the region's economic vitality while safeguarding its cultural heritage. Utilizing the System Usability Scale (SUS) for evaluation, the study involved 23 street vendors and 7 Tourism Awareness Group (Pokdarwis: Kelompok Sadar Wisata). The results were compelling: street vendors recorded a usability score of 72.8, indicating good system functionality, while Pokdarwis achieved an outstanding score of 85, reflecting excellent usability. These outcomes highlight the platform's versatility in meeting diverse user needs and its significant potential in boosting Mandalika's economy. By merging innovative IT solutions with traditional values, this research not only propels economic growth in Mandalika but also sets a scalable and replicable model for similar developments globally, showcasing the transformative power of information technology in regional development.